Mastering Workplace English: A Book Review of 'English for Business Communication' by Mable Chan - MOFFATT, Piangchan; UKE, Waode Ade Sarasmita (Politeknik Negeri Ujung Pandang, 2023)
Although business English books have been extensively published during the last two decades (Bhatia & Bremner, 2012; Emmerson, 2010; Sweeney, 2003; Talbot, 2009), this book,